Off-Pump Tricuspid Valved Stent Implantation: Real-Time Three-Dimensional Transesophageal Echocardiography for Guidance and Assessment. Issue 5 (September 2014) - Pokorny, Saskia; Huenges, Katharina; Gundlach, Jan-Paul; Frank, Derk; Groß, Justus; Cremer, Jochen; Lutter, Georg
In this case report, the value of real-time three-dimensional transesophageal echocardiography (TEE) for guidance and assessment of orthotopic tricuspid valved stent implantation in the beating heart is assessed in four pigs. A full two-dimensional TEE evaluation of standardized parameters was conducted. Three-dimensional TEE provided dependable imaging of anatomical structures of the right side of the heart, the delivery system, and the valved stent, allowing easier orientation and more accurate views for the surgical team. Although visualization of the tricuspid valve in the porcine model is challenging, it contributed highly to the successful implantation of the tricuspid valved stent.